ANALISIS PERPINDAHAN PENGGUNAAN APLIKASI TRANSPORTASI ONLINE MENGGUNAKAN RANTAI MARKOV - K. Nasib, Salmun; Nurwan, Nurwan; Aryasandi, I Wayan Can; K. Hasan, Isran; Asriadi, Asriadi (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2024)
The purpose of this study is to find out the opportunities for switching to the use of online transportation applications and predict the future use of online transportation applications by Gorontalo State University students using the Markov chain. The data used in this study are primary data obtained through questionnaires. The results of the prediction of the proportion for future market share show that the proportion of users of the Maxim transportation application is 82.89%, Grab is 7.75%, Gojek is 5.06% and InDriver is 4.48%.